\[ \large \displaystyle\sum _{ n=1 }^{ k }{ { (-1) }^{ n+1 } } \dbinom{ k }{ n }\displaystyle\sum _{ 1\le i\le j\le n }{ \dfrac { 1 }{ ij } } =\dfrac { 1 }{ { k }^{ 2 } } \]

Prove the equation above.

This is a part of the set Formidable Series and Integrals

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

There are no comments in this discussion.